Revolusi Mental: Penguatan Pendidikan Karakter Dalam Membangun Moralitas Dan Etika Yang Baik Pada Generasi Z - Rialda Safitri Agustina; Maulidyna Aliyyu Fajarani; Heri Septian Pratama; Rhyco Alfian Ramadhon; Aghis Arwa Bekti (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Indonesia as a country with various religions, tribes, cultures, races, customs and so on has values that are believed to be true. These values grew and developed and were passed down from generation to generation by the ancestors of the Indonesian people. Efforts to maintain these values are increasingly being made, one of which was by Ir. Soekarno who initiated a mental revolution, which was also implemented by President Joko Widodo. From the existence of the mental revolution as an effort to strengthen character for the younger generation, especially generation Z, because seeing the current phenomenon that there is a lot of moral degradation among young people. Therefore, this research will discuss the importance of character education for generation Z, as well as the role of family, school, and society in building good morality and ethics in generation Z. The method used in this research is a research study. The method used in this research is a literature study. The data collected will be analyzed using the Miles and Huberman model which includes data collection, data reduction, data presentation, and conclusion drawing. The results of this study are: 1) character education is very important to be given by someone from an early age because it can shape the person to grow up with good character; 2) the role of family, school, and society is also very influential in shaping a person's character, because from the environment, people will see and imitate what is taught in the environment. Therefore, it is important to set a good example so that Generation Z can grow up with good morals and ethics.